Study on the effect of red beetroot (Beta Vulgaris L.) juice intake on some hematological parameters in female rabbits - Zazeia Bilgasim Ali Mohammed Najem , Abdulsalam M. Ghaith (Journal of Pure & Applied Sciences, 2019)
The present study aimed to investigate the influence of red beetroot juice on some hematological parameters in female rabbits. 10 rabbits divided into 2 groups, 5 rabbits each. The first group served as control was given orally (30 ml/day) sterilized distilled water, while the second group was given orally (30 ml/day) fresh juice from red beetroot. Treatment done once daily for 10 and 20 successive days. Blood samples were collected for hematological parameters: total white blood cells (WBCs) count, red blood corpuscles (RBCs) count, platelets (PLT) count, hemoglobin concentration, hematocrit (Hct) value, mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC) were measured. The results showed significant increase in RBCs, hemoglobin concentration and Hct value; while, significant decrease in MCH, MCHC and PLT counts were recorded after administration of beetroot juice for 10 days compared to control group. In contrast, administration of juice for 20 days induced obvious disturbance in the hematological parameters included: significant increase in RBCs, significant decrease in hemoglobin concentration and MCH compared to control group. While, the results showed significant decrease in RBCs, hemoglobin concentration and Hct value, significant increase in MCH and WBCs, also, an improvement in platelet count was demonstrated, after 20 days compared to 10 days. Therefore, beetroot juice can be used by anemia patients and for improvement deficiency in blood cells.